The Influence Of Cash Flow And Profit On Stock Price - Erwin Salim (Institute of Computer Science (IOCS), 2021)
This study examines the impact of cash flow and earnings on stock prices, which seeks to identify the stock price based on its cash flow and profits. The sample in this study is a manufacturing business that went public and was listed on the Indonesia Stock Exchange between 2018 and 2019, utilizing a technical sampling of 15 companies. The analysis was carried out by testing the classical hypotheses and statistical tests to fulfil the assumptions necessary in the multiple linear regression analysis. The traditional assumption tests are multicollinearity, heteroscedasticity, and autocorrelation tests. Then, to establish the level of influence of the independent variable on the dependent variable, a multiple linear regression test was performed. According to hypothesis testing, cash flow and net income positively and significantly affect stock prices. According to the F-test results, the probability value of the cash flow and net income variables is less than Fcount > Ftab. This suggests a positive and strong association between cash flow and net income and stock prices; the better the cash flow and the higher the net income, the higher the stock prices of manufacturing businesses listed on the IDX in 2018-2019. According to the results of the determination, the stock price is controlled by 65.9 percent of the variables, with the remainder influenced by other variables